ALGUNOS DATOS PARA EL ESTUDIO DE LAS BANDAS CIERRE EN EL EPITELIO TIROIDEO - GONZALEZ GUZMAN, IGNACIO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1943)
Natives of central Mexico grind this myriapod with plants to poison arrows The [male] of the sp, when irritated, exudes HCN with a strong odor of bitter almond Ten kg of P vicinus were dried, pulverized and extracted 4 times with ethyl alcohol A yel
BOL INST ESTUD MED BIOL
Keywords: DATOS, ESTUDIO, BANDAS, CIERRE, EPITELIO, TIROIDEO; CIENCIAS MEDICAS; MEDICINA INTERNA; ENDOCRINOLOGIA